2015
DOI: 10.1155/2015/860259
|View full text |Cite
|
Sign up to set email alerts
|

Xuebijing Ameliorates Sepsis-Induced Lung Injury by Downregulating HMGB1 and RAGE Expressions in Mice

Abstract: Xuebijing (XBJ) injection, a traditional Chinese medicine, has been reported as a promising approach in the treatment of sepsis in China. However, its actual molecular mechanisms in sepsis-induced lung injury are yet unknown. Therefore, this study aimed to investigate the beneficial effects of XBJ on inflammation and the underlying mechanisms in a model of caecal ligation and puncture-(CLP-) induced lung injury. The mice were divided into CLP group, CLP+XBJ group (XBJ, 4 mL/kg per 12 hours), and sham group. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Apatinib, also known as YN968D1, is a small molecule TKI that mainly targets VEGFR‐2 through the intracellular ATP‐binding site that inhibits all VEGF‐stimulated endothelial cell migration and proliferation, decreases tumor microvascular density, and promotes apoptosis . On 17 October 17, 2014, apatinib was approved by the cFDA as a third or subsequent‐line therapy for advanced or metastatic chemo‐refractory gastric cancer . Both preclinical and clinical studies have shown that apatinib has promising efficacy, convenient oral administration methods, and manageable AEs in the treatment of a variety of solid tumors …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apatinib, also known as YN968D1, is a small molecule TKI that mainly targets VEGFR‐2 through the intracellular ATP‐binding site that inhibits all VEGF‐stimulated endothelial cell migration and proliferation, decreases tumor microvascular density, and promotes apoptosis . On 17 October 17, 2014, apatinib was approved by the cFDA as a third or subsequent‐line therapy for advanced or metastatic chemo‐refractory gastric cancer . Both preclinical and clinical studies have shown that apatinib has promising efficacy, convenient oral administration methods, and manageable AEs in the treatment of a variety of solid tumors …”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] On 17 October 17, 2014, apatinib was approved by the cFDA as a third or subsequent-line therapy for advanced or metastatic chemo-refractory gastric cancer. 49 Both preclinical and clinical studies have shown that apatinib has promising efficacy, convenient oral administration methods, and manageable AEs in the treatment of a variety of solid tumors. 26,32,33,50 The efficacy of apatinib as a second or subsequent-line therapy in patients with advanced NSCLC has been investigated in several studies.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with the HMGB1, RAGE, one of the surface receptors in cytomembrane, also can trigger the development of inflammatory cascade including mitogen-activated protein kinases (MAPK), TLR4 and NF-kB translocation. [21][22][23][24][25] Previous studies have shown that RAGE could mediate the HMGB1 activation of TLR4 and TLR2 signal transduction and the development of ALI after hemorrhagic shock. 15,16,18 The present study demonstrated that both mRNA and protein expressions of RAGE are increased in hemorrhagic shocked kidneys and that these increases are abolished by PHSML drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies support this assertion, such as the study by Matsumoto et al [40] demonstrated that the sRAGE serum level of patients with sepsis increases directly proportional to the severity of the disease, suggesting that sRAGE reflects on the RAGE's signaling pathway inducing an excessive inflammatory response involved in endothelial injury and coagulopathy. In the same year, Wang et al [41] demonstrated that the decrease in sRAGE levels in mice results in improved sepsis-induced lung damage, thus decreasing mortality in this condition. Another study by Narvaez-Rivera et al [36] demonstrated in 2015 that sRAGE's level in the plasma is high in patients with communityacquired pneumonia associated with sepsis and is also an independent factor for the likelihood of a fatal outcome.…”
Section: Promising Biomarkers 31 Receptor For Advanced Glycation Endmentioning
confidence: 99%